The Influence of Culture on the Disposition Effect. Individual assignment - Kishta, Mohammed (2013)
This paper is intended to examine, compare, and justify the degree of disposition effect present in individuals of three different cultures, Chinese, Indian and Arab. ␣␣␣␣ ␣␣␣␣␣␣␣␣ ␣␣␣␣␣ ␣␣␣␣␣␣␣␣␣␣ ␣␣␣ ␣␣␣ ␣␣␣␣␣␣␣␣␣␣␣␣ ␣␣␣␣␣␣␣␣ ␣␣␣␣␣␣␣␣ has a significant influence on the degree of disposition effect, that is, the fact that investors seem to hold on to their losing stocks to a greater extent than they hold their winning stocks. We examine the effect of culture on this behavioural phenomena using a devised excel program game that replicates a real stock market environment. As a control procedure, we made sure that all participants in our experiment had a background in finance and share the same demographics in terms of age, experience, and occupation (University students).